Analisis Pengaruh Angkatan Kerja Yang Tidak Tamat SD Terhadap IPM Kabupaten Lombok Barat Tahun 2018 - Ahmad Suhendri; Baehaqi Baehaqi (Universitas Hamzanwadi, 2023)
The aim of this research is : (1) to describes the distribution of the workforce in the West Lombok Regency who did not complete elementary education or its equivalent; (2) to analyze the HDI projection for West Lombok Regency based on the increase in the duration of education of the workforce who was not complete elementary school or equivalent (Education Index); and (3) to analyze the strategies of enhancement the average length of school age/workforce population in West Lombok Regency, especially those who was not complete elementary school or equivalent. The method of this study employed a survey approach using data from Monte Carlo simulations. The results of the research were ; (1) human development in West Lombok Regency continues to progress marked by the improvement in the Human Development Index (HDI) from 66.37 in 2017 to 67.18 in 2018 or an increase of 0.81%; (2) West Lombok HDI is predicted from the three forming variables the Education Index, Health Index, and Income Index, respectively. The increasing trend for the education index was 1.557, the health index will increase by 0.425 and the income index will increase by 0.623; (3) Statistical test results by Monte Carlo simulation data showed that the three formed variables of the HDI had a positive effect on the West Lombok HDI, both individually and simultaneously.